Charge-collection efficiency and long-term stability of single-crystal CVD diamond detector under different carrier-drift conditions. (4th March 2016) - Sato, Yuki; Murakami, Hiroyuki; Shimaoka, Takehiro; Tsubota, Masakatsu; Kaneko, Junichi H.
Abstract: We investigate the performance of a charged-particle detector fabricated using single-crystal diamond grown by chemical vapor deposition. The detector identified four different 241 Am α-particle energies (5.389, 5.443, 5.486, and 5.545 MeV) thanks to its superior energy resolution of 0.407 ± 0.004% for electron drift and 0.418 ± 0.004% for hole drift (full width at half maximum). The charge-collection efficiency inside the diamond crystal was above 97.0% for both electrons and holes. The diamond detector also exhibited no significant degradation in terms of pulse-height spectra and energy resolution during operation for more than 100 h under electron-drift conditions. In contrast, the pulse-height spectra obtained under hole-drift conditions deteriorated because of the polarization phenomenon.